Frequency Conversion of Optical Vortex Arrays Through Four-Wave Mixing in Hot Atomic Gases - Mendoza-López, L. A.; Acosta-Montes, J. G.; Bernal-Orozco, J. A.; Torres, Y. M.; Arias-Téllez, N.; Jáuregui, R.; Sánchez, D. Sahagún (Frontiers in Physics, 2022)
Arrays of multiple vortices were transferred from infrared to the blue region of the optical spectrum. This demonstration was achieved by inducing four-wave mixing in an atomic gas with a Gaussian beam and a quasi-invariant propagation beam of the Mathieu type. The later structure was analyzed in the Fourier space for both the pump and the generated light. In both cases the phase structure can be written with a compact mathematical expression by using the same parameters within the experimental error bars. A Michelson-Morley interferometer was used to confirm that a phase singularity was present at each site predicted by theory. These studies add to the available control over orbital angular momentum in photons generated by atoms, that has a broad spam of applications on quantum and classical information management.